Lietuvos internetinės žiniasklaidos konstruojamo politinio diskurso kaita - Matkevičienė, Renata (Information & Media, 2012)
Jau gerą pusę šimtmečio mokslininkų tyrimais yra įrodyta, jog žiniasklaida yra aktyvi politinio diskurso dalyvė ir konstruotoja. Praėjusio šimtmečio pabaigoje įsivyravus internetinei žiniasklaidai matomi ir žiniasklaidos turinio formavimo bei informacijos pateikimo pasikeitimai. Įsivyravus informacinėms technologijoms, keičiasi ne tik žiniasklaida, jos veikla, kuriamas ir skleidžiamas turinys, bet ir komunikacija, į kurią yra įtraukti ir kiti viešosios erdvės veikėjai – visuomenė ir politikai. Pastarųjų sąveika politikos komunikacijos sistemoje geriausiai atsispindi būtent per žiniasklaidoje pateikiamą informaciją, jos pranešimų poveikį ir pan., nes daugiausia tik dėl žiniasklaidoje pateikiamų pranešimų yra įmanomas visuomenės informuotumas apie politiką, taip pat tik žiniasklaida įtraukia visuomenę į politinių sprendimų priėmimą ar diskusiją apie politines problemas, priimamus sprendimus. Šiame straipsnyje nėra kvestionuojamas žiniasklaidos, taip pat ir internetinės žiniasklaidos, vaidmuo, jos svarba ar poveikiai, straipsnyje yra teigiama, kad žiniasklaida, o ypač internetinė, yra aktyvi politinės komunikacijos dalyvė, įtraukianti į aktyvią komunikaciją ir politikus per jų pasisakymams suteikiamą erdvę. Dėl šių veiksmų, internetinėje žiniasklaidoje pastebimas ne tik žiniasklaidos formuojamas politinis turinys, bet ir pačių politikų konstruojamas politinis diskursas, kurį žiniasklaida tik moderuoja. Šio straipsnio tikslas – ištirti ir nustatyti internetinėje žiniasklaidoje pateikiamo politinio diskurso kaitą. Aptariamas žiniasklaidos vaidmuo ir jo kaita politikos diskurso konstruotojamame politikos komunikacijos kontekste, taip pat siekiama nustatyti internetinės žiniasklaidos politinio diskurso, konstruojamo pačių politikos veikėjų, kaitą. Changes in the Political Discourse Constructed by the Lithuanian Internet Media Renata Matkevičienė Summary In the end of the last century when the social media became an important part of the media system, there oceurzed changes in constructing the content the of media and spread of information, as well as news creation, selection and delivery. Changes that occurred in the media because of new information technologies could be seen not only in the mass media, journalism, but also in communication in general, because those changes involved all participants of the public sphere: the media, politicians and citizens. In the system of political communication, the interaction of these participants could be seen via the news that are delivered, and their effects: society receives information about politics and participates in discussions about it. In the article, the role and effects of the Internet are not questioned, because the Internet media are an active participant of political communication; they involve politicians into communication processes, providing space for their voices (publications). The aim of this article is to analyse the change of political discourse in the Internet media content. In the article, the role of the media and its change are discussed in the context of social constructivist theoretical approach; also the political discourse constructed by and in the internet media is analyzed in search of changes in the construction of political discourse, introduced by politicians into the Internet media. The main conclusions made in the article are as follows: 1) the use of the internet by politicians as an arena for discussions is increasing, 2) the main topics discussed by politicians in the internet are politics, economy, energy and social policy, 3) the ways in which politicians are discussing political issues differ depending on the number of years that a politician participates in the political arena, the topic or issue under discussion, 4) economic and political issues are discussed in more sophisticated ways in comparison with discussions of social policy issues which are presented in a very simple, clear way with the arguments that stress the aspects important for society or for some specific groups of citizens, 5) in presenting ideas and in discussions, the politicians prefer to present their own the position instead of presenting position of a political party. These main research findings lead to some conclusions about changes in the political discourse, but they also show quite a strong and manipulative role of the Internet media in selecting politicians and their publications, so it shows that there is still a strong role of the Internet media in constructing the political reality and presenting this “window” to political reality, which is strongly influenced by the position of the media.